Analisis Komparatif Strategi Komunikasi Krisis pada Platform Crowdfunding di Indonesia - Dara Puspita Sari (Communicology: Jurnal Ilmu Komunikasi, 2025)
The rapid growth of digital philanthropy in Indonesia through crowdfunding platforms has transformed public participation in donation activities, while simultaneously increasing reputational risks related to transparency issues and potential misuse of funds by third parties. Although previous studies have extensively examined donor behavior, platform technology, and trust formation, research on reputation crisis management in crowdfunding platforms remains limited. Therefore, this study aims to analyze the crisis communication strategies implemented by Kitabisa in responding to reputational issues. This research employs a qualitative approach using a comparative case study method focusing on two incidents: the misunderstanding of donation distribution that went viral through the X account @deddyhuang_ (2023) and the alleged misuse of donations by Singgih Sahara (2024). The analysis is guided by Situational Crisis Communication Theory (SCCT), particularly the Crisis Reputation Interventions Continuum. Data were collected through in-depth interviews, digital media observation, and document analysis, and were analyzed using thematic analysis techniques. The findings reveal that Kitabisa adapts its crisis communication strategies situationally, ranging from diminish to rebuild strategies, depending on the level of public responsibility attribution and the severity of reputational threats. This study concludes that crisis communication in digital philanthropy platforms functions not merely as a technical response, but as a strategic reputational intervention to maintain public trust and institutional legitimacy.